Analysis of Factors Influencing Studentpreneur Behavior Among Vocational High School Students - Khairunnisa, Rosyidah; Suparno, Suparno; Nurjanah, Siti (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to determine the factors that influence the formation of studentpreneur behavior. The research was conducted using a quantitative approach and analyzed using the Smart PLS 4.0 program. The population in this study were Vocational High School Students from 3 schools in North Jakarta, namely SMKN 12 Jakarta, SMK 49 Jakarta, and SMK Walang Jaya with a total sample of 136 students. Data was obtained using a questionnaire with 33 closed statements using a likert scale with 5 alternative answers. The test results show that there is a direct significant influence of entrepreneurship education (p = 0.015), social support (p = 0.003), and self-efficacy (p = 0.000) on studentpreneur behavior. In addition, there is a direct significant effect of entrepreneurship education (p = 0.001) and social support (p = 0.000) on self-efficacy. Furthermore, it was found that self-efficacy has a significant mediating role in the influence of entrepreneurship education on studentpreneur behavior (p = 0.024) and also in the influence of social support on studentpreneur behavior (p = 0.002).